(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Dermatoglyphics, the study of fingerprint patterns, offers valuable insights into individual identity, with each person having a unique and permanent fingerprint design. These patterns are shaped by both genetic and environmental influences during fetal development. The aim of this research was to explore the relationship between fingerprint patterns and human behavioral traits. Materials and methods: This descriptive cross-sectional study aimed to explore the relationship between sociodemographic factors (Age, gender, blood group and handedness) in medical students through fingerprint analysis. Conducted at Southern Medical College in Chattogram, Bangladesh, the study included 350 undergraduate students from the 1st to 5th year selected using census sampling. Data were collected using a structured questionnaire and fingerprint analysis. Descriptive statistics and the Chi-square test were used for analysis. Ethical approval was obtained from the Institutional Review Board (IRB) prior to the study. Results: The study analyzed the socio-demographic profile and fingerprint patterns of 350 students, revealing a mean age of 21.49 years, with a higher proportion of females (57.7%). The most common fingerprint pattern across all fingers was whorls, particularly on the right thumb (59.4%). Significant associations were found between the right thumb’s fingerprint patterns and various personality traits, including Openness to Experience, Conscientiousness, Extraversion, Agreeableness, and Neuroticism. Notable correlations were observed for traits like indulging in fancies (p=0.000) helping others (p=0.000) and bursts of rage (p=0.000) suggesting that fingerprint patterns, particularly whorls, may be linked to personality characteristics. Conclusion: This study reveals significant associations between right thumb fingerprint patterns, especially whorls and personality traits like Openness to Experience, Conscientiousness, Extraversion, Agreeableness and Neuroticism. JCMCTA 2025 ; 36 (1) : 141-146